Perceived Organizational Support (POS) With Home Industry Employee Organizational Commitment - Belsa Azizih Fajar Amabel; Ramon Ananda Paryontri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Effective human resource management can increase employee productivity and performance. A person's success and performance in doing work is influenced by his sense of commitment to work. Some of the phenomena that occur in the bag home industry in Tanggulangin are the emergence of negative perceptions in employees towards the home industry and the impact on work processes that are not optimal. This study aims to determine the relationship between perceived organizational support (POS) and organizational commitment. This study used a quantitative approach and used a random sampling technique with 150 respondents. The data collection method uses a Likert scale with 34 item perceived organizational support (POS) scale and 24 item organizational commitment scale. The data analysis technique uses the pearson product moment correlation test. The results show that the value of Sig. (2-tailed) o.oo1 (<0.05) and a value of r=o.433 which explains that perceived organization support (POS) is positively related to Organizational Commitment with a moderate degree of correlation. The correlation test stated that the Pearsons correlation value was greater, namely 0.433 when compared to the r table value, which was 0.159. This means that there is a relationship between the variables perceived organization support (POS) and Organizational Commitment. The higher the Perceived Organizational Support (POS), the higher the level of commitment to the organization.Pengelolaan sumber daya manusia yang efektif dapat meningkatkan produktivitas serta kinerja karyawan. Keberhasilan dan kinerja seseorang dalam melakukan pekerjaan dipengaruhi oleh rasa komitmennya terhadap pekerjaan. Beberapa fenomena yang terjadi pada home industri tas di Tanggulangin yaitu munculnya persepsi negatif dalam diri karyawan terhadap home industri dan berdampak pada proses bekerja yang tidak maksimal. Penelitian ini bertujuan untuk mengetahui hubungan antara perceived organizational support (POS) dengan komitmen organisasi. Penelitian ini menggunakan pendekatan kuantitatif dan menggunakan teknik random sampling dengan 150 responden. Metode pengumpulan data menggunakan skala likert dengan skala perceived organizational support (POS) 34 aitem dan skala komitmen organisasi 24 aitem. Teknik analisis data menggunakan uji korelasi pearson product moment. Hasil menunjukkan bahwa nilai Sig. (2-tailed) o.oo1 (<0.05) dan nilai r=o.433 yang menjelaskan bahwa perceived organization support (POS) berhubungan secara positif dengan Komitmen Organisasi dengan derajat hubungan korelasi sedang. Uji korelasi menyatakan nilai pearsons correlation lebih besar yakni 0,433 jika dibandingkan dengan nilai r tabel yakni 0,159. Artinya terdapat hubungan antara variabel perceived organization support (POS) dan Komitmen Organisasi. Semakin tinggi Perceived Organizational Support (POS) maka semakin tinggi tingkat komitmen terhadap organisasi.